A cartografia tátil na escola: outras perspectivas sobre o ensino de geografia - Rodrigues, Laís Caroline (Universidade Federal de São Carlos, 2021)
Increasingly present in society, maps gain more prominence in everyday school life. But often, reading these materials is hampered by the high level of abstraction required due to the technical language used. Therefore, new possibilities for the use of cartographic language in the teaching of geography in schools are sought. Therefore, Tactile Cartography, a branch of School Cartography specializing in the making of tactile cartographic materials for the teaching of geography for people with visual impairment, emerges as a possible path for the perception of the landscape and the construction of the concept of space, playing an important role mainly for the blind or low vision student. This work aims to reflect on how tactile representations can contribute to the teaching and learning of Geography for all types of students, regardless of visual acuity. Through the preparation and application of tactile maps and their use in the classroom, based on the action-research method, based on artisanal techniques, we seek to develop materials that dialogue with the reality of the student in everyday life and in school life. Because it is easy to assimilate and accessible to all students, the tactile graphic language allows for a more inclusive approach in terms of understanding the contents covered in the classroom. More than a specific cartography for certain types of students, Tactile Cartography demonstrates competence in school practice, not only for Geography, but to work in different areas of knowledge and truly form an inclusive school that encompasses and integrates all students. Exploring a multisensory methodology, the maps worked during the research showed more effectiveness in understanding the contents in the teaching and learning process of Geography than those presented in textbooks. More objective and with a more simplified reading, the students were able to assimilate the knowledge that was asked for reflection and elaboration of the exercises, corroborating for the confirmation of the perceptions that motivated this research. Thus, the aim is to contribute to the advancement of research in Tactile Cartography, in directing discussions for the development and use of tactile graphic language at school.
The tactile cartography at school: other perspectives about the teaching of Geography.
Keywords: Cartografia tátil; Cartografia escolar; Ensino de Geografia; Tactile cartography; School cartography; Teaching geography; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO